ANALISIS KEARIFAN LOCAL SEBAGAI MANIFESTASI NILAI PANCASILA DALAM KEHIDUPAN SOSIAL MASYARAKAT ADAT (STUDI DI DUSUN SADE KABUPATEN LOMBOK TENGAH) - I Nengah Arisudhana Widnyana; Mahedra, M. Afkar; Neneng Mutmainnah; Lisatullaeli; Izzati, Nurul; Ulfatunnisah; Muh. Zubair (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to evaluate how local wisdom in Sade Hamlet plays a role as a real implementation of Pancasila values in the social life of the community. In this study, the researcher used a qualitative research approach. The method used in this study is a qualitative descriptive approach, there are three main methods, namely interviews, observation, and documentation. The subject of the study was the head of Sade Hamlet, the results of the study ANALYSIS OF LOCAL WISDOM AS A MANIFESTATION OF PANCASILA VALUES IN THE SOCIAL LIFE OF INDIGENOUS COMMUNITIES (STUDY IN SADE HOME, CENTRAL LOMBOK REGENCY) consists of several aspects, namely: 1. Dynamics of the Sade Hamlet Community in Maintaining Local Wisdom in the Midst of Modernization. 2. Effectiveness of Sade Hamlet Local Wisdom in Strengthening Pancasila Values Through Traditional Activities. 3. Reflection of Traditional Values in the Local Wisdom of the Sade Hamlet Indigenous Community.